LEVEL OF CONFORMITY EXAMINATION OF URIC ACID LEVELS IN PLEURAL FLUID, RATIO OF URIC ACID LEVELS IN PLEURAL FLUID WITH SERUM TO DISTINGUISH EXUDATES AND TRANSUDATES - Sigit, Indarto; Sutanto, Yusup Subagio; Harsini, Harsini (Perhimpunan Dokter Paru Indonesia (PDPI)/The Indonesian Society of Respirology (ISR), 2020)
Background: Uric acid can be used as a biomarker to distinguish transudates from pleural fluid exudates. Uric acid is soluble in liquid media, elevated levels of uric acid in blood plasma become a predisposing factor for uric crystal deposits in tissues and body fluids. Increased permeability due to changes in capillary pleural pressure in the formation of transudates is a cause of increased levels of uric acid in pleural fluid. The aim of the study was to analyze the examination of pleural fluid uric acid levels and the ratio of uric acid levels to pleural fluid to serum to distinguish exudates and transudates in pleural effusion. Methods: A cross sectional diagnostic test with a cross sectional study design in pleural effusion patients at RSUD Dr. Moewardi Surakarta in July-August 2019. Subjects were examined for pleural fluid levels, serum uric acid ratio, and pleural fluid analysis. Results: A total of 30 pleural effusion patients were included in this study. The level of agreement between the uric acid pleural fluid against Light criteria was in the moderate category and statistically significant (Kappa = 0.595; P=0.001). The level of agreement between the ratio of uric acid to pleural fluid and serum to Light's criteria was weak and not statistically significant (Kappa = 0.200; p = 0.195) Conclusion: The level of concordance between pleural fluid uric acid with Light criteria is in the medium category and statistically significant. There is no match between the ratio of serum pleural fluid uric acid levels with Light criteria. (J Respir Indo. 2020; 40(2): 82-6)